Acoustic Measurements on a Sonic Crystals Barrier. (November 2015) - Morandi, Federica; Miniaci, Marco; Guidorzi, Paolo; Marzani, Alessandro; Garai, Massimo
Abstract: This paper describes the measurements carried out over a sonic crystal at normal incidence according to EN 1793-6, which allows to cancel ground reflection and edge diffraction by applying suitable windowing techniques. The sample was made of hollow PVC pipes with an outer diameter of 160 mm arranged in a square lattice with lattice constant 0.2 m. FE predictions were computed in order to verify the experimental campaign. A good match between simulations and measurements was found in the first sonic Bragg band gap. As expected, increasing the number of rows does not translate into a shift of the Bragg band gap but into an increase of the insulation properties.